Pengaruh Kualitas Produk,Citra Merek,Dan Gaya Hidup Terhadap Keputusan Pembelian Produk H&M - Davin Sean; Amron Amron (Jurnal Mirai Management, 2022)
The development of Indonesian consumers' assessment of fashion and how to dress has accelerated the development of the clothing product market. With the needs of the community, namely social, lifestyle, political, economic and cultural, it can also create new fashions. Indonesians like lifestyles that keep up with the times, increasing demand for products clothes. This study used a collection technique with a questionnaire with a total sample of 100 respondents using a purposive sampling technique. And the data analysis technique used is multiple linear regression analysis. Data will be used IBM SPSS 24 software. These results indicate that product quality and lifestyle influence H&M purchasing decisions, and brand image does not influence H&M product purchasing decisions. Kata Kunci : Product Quality, Brand Image, Lifestyle, Purchase Decision